Acute exposure to leucine modifies behavioral parameters and cholinergic activity in zebrafish. Issue 78 (November 2019) - Wessler, Leticia B.; Farias, Hemelin R.; Ronsani, Julia F.; Candiotto, Gabriela; dos Santos, Paulo C.L.; de Oliveira, Jade; Rico, Eduardo P.; Streck, Emilio L.
Highlights: Zebrafish acutely exposed to leucine as model of Maple Syrup Urine Disease. Zebrafish exposed to leucine presented anxiety-like behavioral. Anxiety-like behavioral caused by leucine is associated with cholinergic imbalance. Abstract: Maple Syrup Urine Disease (MSUD) is an autosomal recessive inherited disorder, caused by a deficiency on branched chain α-ketoacid dehydrogenase complex activity, resulting in accumulation of branched-chain amino acids (BCAA) (e.g. leucine). The treatment of MSDU patients increases survival time and quality of life. Thus, nowadays there are a crescent number of adolescents and adults with MSUD. Relevant studies have been reported behavioral alterations in these patients, i.e. high risk of chronic neuropsychiatric problems, such as attention deficit disorder, depression and anxiety. Moreover, MSUD is associated to neurotransmitters deficiency. Herein, we aimed to investigate whether the toxicity of leucine is associated to anxiety-like behavioral, using zebrafish acutely exposed to leucine as experimental model of MSUD. In addition, we evaluated the effects of high levels of leucine in the acetylcholinesterase (AChE) and choline acetyltransferase (ChAT) activities, components of cholinergic neurotransmission system. Young zebrafish were exposed to 2 mM and 5 mM concentration of leucine for 24 h. After that, the animals were submitted to the Novel Tank test, having the brain collected to enzymatic determination. The exposure to both concentrations of leucine caused behavioral and brain cholinergic activity alterations in young zebrafish, indicating an anxiety-like behavior and cholinergic dysfunction. Therefore, this animal could be considered a promising organism to study the BCAA neurotoxic effects, which could help to a better comprehension of the behavioral and neurochemical alterations present in patients with MSUD.